Brazilian Aphidoidea: II. Accounts of the lachninae, chaitophorinae, greenideinae, anoeciinae, and hormaphidinae - Costa, Claudio L.; Eastop, V. F.; Blackman, Roger L. (Pesquisa Agropecuaria Brasileira, 1993)
Keys are provided for the identification of the tribes, genera and species of Brazilian Lachninae, Chaitophorinae, Greenideinae, Anoeciinae and Hormaphidinae. Host plant and distribution data are given for each species.